Maintaining the Blessing of Business: An Analysis of Digital Marketing within the Framework of Maqashid Sharia - Mutaufiq, Ali; Hardiana, Candra Dwi; Lestari, Novi (Pasundan Social Science Development, 2025)
The rapid development of digital technology has significantly influenced business strategies, especially in marketing practices. In the Islamic perspective, marketing is not solely evaluated based on efficiency and profit, but also on its alignment with principles of maqashid sharia to ensure blessings (barakah) for both businesses and consumers. This article aims to analyze digital marketing through the lens of maqashid sharia, which encompasses five essential elements: the protection of religion (hifzh al-din), life (hifzh al-nafs), intellect (hifzh al-‘aql), wealth (hifzh al-mal), and lineage (hifzh al-nasl). By utilizing a descriptive qualitative approach with library research, this study explores how the integration of maqashid sharia can guide ethical and just business practices in digital marketing. The findings suggest that embedding maqashid sharia into digital marketing strategies promotes not only material success but also spiritual and ethical prosperity, ensuring a holistic and sustainable business model. This research contributes to the contemporary literature on Islamic economics, proposing a framework for businesses to navigate digital marketing in a way that is both ethically sound and aligned with Islamic values.